Introduction to Chemical Engineering Thermodynamics - Smith (J M); Ness (Van H C); Abbott (M M) (2005)
Chemical Engineering ; Thermodynamics
41643a.jpg;41643b.jpg;41643c.jpg;41643d.jpg
22.5
Keywords: Chemical Engineering ; Thermodynamics